The role of inflammatory factors in the tumortransformation of the endometrium - N A Sheshukova; T D Guriev; A S Fedotova (IP Berlin A.V., 2014)
On the basis of immunohistochemical studies the role of chronic endometritis in the potentiation of the proliferative activity of the endometrium was demonstrated; defined and denoted were the values of the chronic inflammatory process in the endometrium, as an independent factor determining the prognosis of the disease.